2016
DOI: 10.3892/mmr.2016.5763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polysaccharides isolated from Inonotus obliquus against hydrogen peroxide-induced oxidative damage in RINm5F pancreatic β-cells

Abstract: The purpose of the present study was to elucidate the cytoprotective effects of polysaccharides isolated from Inonotus obliquus. The polysaccharides were extracted from the fruiting body of I. obliquus (PFIO) and the liquid culture broth of I. obliquus (PLIO). The effects of PFIO and PLIO on hydrogen peroxide (H2O2)‑induced oxidative damage of RINm5F pancreatic β‑cells were comparatively investigated using an MTT assay, immunofluorescent staining, flow cytometry, and western blot analyses in vitro. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Via the regulation of mitogen-activated protein kinases, nuclear factor (NF)–κB, and apoptotic proteins, polysaccharides isolated from the fruiting body of I . obliquus inhibited the hydrogen peroxide–induced oxidative damage in RINm5F pancreatic β-cells [17]. The ethanol extract from the dry matter of a culture broth of I .…”
Section: Introductionmentioning
confidence: 99%
“…Via the regulation of mitogen-activated protein kinases, nuclear factor (NF)–κB, and apoptotic proteins, polysaccharides isolated from the fruiting body of I . obliquus inhibited the hydrogen peroxide–induced oxidative damage in RINm5F pancreatic β-cells [17]. The ethanol extract from the dry matter of a culture broth of I .…”
Section: Introductionmentioning
confidence: 99%
“…The IOP monomers revealed by GC analysis comprised certain unique sugars, including arabinose, xylulose, ribose, rhamnose, and glucose ( Figure 7 ) that are known to be components of branched polysaccharides, such as β-glucan, which is reported to possess several health benefits [ 25 ]. β-glucan has been reported to have anti-diabetic, anti-proliferative properties, and anti-tumorigenic properties [ 26 ]. Such beneficial effects could be attributed to the ability of β-glucan to scavenge free radicals generated due to endogenous or exogenous agents, such as ionizing UVB radiation, thereby assisting the cells to repair DNA [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recent surge in medicinal mushrooms because of their unique inherent beneficial attributes such as anti-inflammatory, anti-tumor, anti-oxidant, and anti-diabetic properties has been noteworthy 10,14,17,18 . Chaga mushroom is one such mushroom that is considered to be one of the highest anti-oxidant compounds 19 and possess several such beneficial properties. In the present study, we showed that the hot water extract of the Chaga mushroom polysaccharides significantly reduced apoptosis and the generation of intracellular ROS that protected the cellular DNA from oxidative damage, in addition to enhancing the development of zebrafish.…”
Section: Discussionmentioning
confidence: 99%